Salesian streetworking with children: The specificity of interventions in the international perspective - research on internet sites - Bogdan Wiesław Stańkowski (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Salesian educational work with street children has its origins in the educational practice of Fr. Bosco. Currently, hundreds of Salesians around the world are involved in education of street children. Salesians' commitment to working with street children is a clear example of the continuation of Fr. Bosco's practice of working with the poor and homeless children and with those without prospects for the future. In this article, the author seeks to look at the specificities of Salesian educators' influence on children and adolescents (methods of action while working with street children, goals). The theoretical part will be enriched with qualitative research conducted in May 2017. The research results are based on an analysis of the content of the available websites in dozens of countries in the world.